Policy and Strategies of Tariff Incentives Related to Renewable Energy: Comparison between Indonesia and Other Developing and Developed Countries - Supriyanto, Eko; Sentanuhady, Jayan; Hasan, Wisnu Hozaifa; Nugraha, Ariyana Dwiputra; Muflikhun, Muhammad Akhsin (MDPI AG, 2022)
The transition from conventional fossil fuels to renewable energy is necessary, along with the increase in energy consumption and the decline in national energy production. In its application, increasing the renewable energy mix has many challenges, especially cost-efficiency. Thus, to make renewable energy competitive and achieve a significant acceleration of the mix, massive energy incentive policies are being studied and developed. This study provided a specific overview of policies and strategies for tariff incentives related to renewable energy, particularly in developing and developed countries. An essential section of this study discusses the comparison between Indonesia and other countries, as well as the current status and an ideal policy related to renewable energy for this country. The implementation of energy incentive policies in each country is quite different, depending on the potential, technological readiness, and political and economic conditions. Compared with other policy mechanisms such as RPS, FIT policies are more efficient at increasing capacity and stimulating R&D inputs to reduce costs. In terms of the stage of economic development and characteristics of the electricity system, the price adjustment model, such as that used in East Asia, is more suitable for application in Indonesia than other models. © 2022 by the authors.